Karakteristik Kejadian Gagal Jantung Kongesti (GJK) pada Pasien Diabetes Mellitus Tipe 2 (DM tipe 2) di RSUD Al-Ihsan Bandung Tahun 2019-2020 - Muhammad Rifqi Khairul Ummam; Sadiah Achmad; Ratna Dewi Indiastuti (Bandung Conference Series: Medical Science, 2022)
Abstract. Congestive heart failure (CHF) is a functional or structural heart disorder that interferes with ventricular filling or ejection of blood into the systemic circulation. The risk factors for CHF are age and gender. The purpose of this study was to analyze the incidence of congestive heart failure in type 2 DM patients at the outpatient polyclinic of Al-Ihsan Hospital, Bandung. This study is an analytic observational with a cross-sectional approach. The sampling technique used was purposive sampling from medical record data with a total sample of 80 people who entered the inclusive criteria. Data analysis using Chi-square test. The results of the study described CHF patients as 22.5%. Type 2 DM patients experienced CHF 16.25%, and male 6.25%. The age of type 2 DM patients who experienced the most CHF was in the range of 55-64 as much as 10.00%. From this study, it was concluded that the characteristics of type 2 DM patients at the Al-Ihsan outpatient polyclinic who experienced CHF were women experiencing CHF more than men and the age of type 2 DM patients who experienced CHF was mostly in the range of 55-64 years. Abstrak. Gagal jantung kongesti (GJK) adalah gangguan fungsional atau struktural jantung yang mengganggu pengisian ventrikel atau ejeksi darah ke sirkulasi sistemik. Faktor risiko terjadinya GJK adalah usia dan jenis kelamin. Tujuan penelitian ini adalah untuk menganalisis kejadian gagal jantung kongesti pada pasien DM tipe 2 di poliklinik rawat jalan RSUD Al-Ihsan, Bandung. Penelitian ini merupakan observasinal analitik dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan Purposive Sampling dari data rekam medik dengan jumlah sampel sebanyak 80 orang yang masuk kriteria inklusif. Analisis data menggunakan uji Chi-square. Hasil penelitian menggambarkan pasien GJK 22.5%. Pasien DM tipe 2 perempuan yang mengalami GJK 16.25%, dan laki-laki 6.25%. Usia pasien DM tipe 2 yang terbanyakmmengalami GJK pada rentang 55-64 sebanyak 10.00%. Dari penelitian ini didapatkan kesimpulan bahwa karakteristik pasien DM tipe 2 di poliklinik rawat jalan Al-Ihsan yang mengalami GJK adalah perempuan lebih banyak mengalami GJK daripada laki-laki dan usia penderita DM tipe 2 yang mengalami GJK terbanyak pada rentang 55-64 tahun.